China Galileo Test Range and Its Critical Technologies - 刘学林 蔚保国 (Transactions of Tianjin University, 2009)
With the rapid development of global navigation satellite system （GNSS） and its applications, GNSS test range is becoming the focus of research. This paper, with the cooperation on Galileo Program between Europe and China as background, gives an overview of the development of test ranges for satellite navigation, proposes an implementation plan for China Galileo Test Range （CGTR）, presents an analysis of CGTR and describes its overall objective, architecture, function and services, as well as operating modes. Particular analysis and study are given to the critical technologies related to CGTR implementation, including test range simulation and evaluation, time synchronizing and keeping, and pseudolite time division multiple access （TDMA） signal design. Research results of this paper can be helpful to GNSS testing and related applications.